Penetapan Kadar Kurkuminoid Dalam Jamu Serbuk Yang Mengandung Simplisia Rimpang Kunyit (Curcuma domestica Val.) yang Beredar di Kota Medan - Siregar, Muhammad Alfariz Baihaqi; Harun , Fathur Rahman; Ridwanto, Ridwanto; Daulay , Anny Sartika (Journal of Pharmaceutical and Sciences, 2026)
Background: Kunir asem herbal medicine is a traditional beverage widely consumed by the community to relieve menstrual pain due to the content of turmeric (Curcuma domestica Val.) which contains active compounds with analgesic, antipyretic, and anti-inflammatory properties. However, information regarding curcuminoid levels in powdered herbal medicine products circulating in the community remains limited, particularly in Medan City. Objective: This study aimed to identify the presence of curcuminoids in powdered herbal medicine containing turmeric rhizome circulating in Medan City and to determine the compliance of their levels with quality requirements according to the Indonesian Herbal Pharmacopoeia Second Edition 2017. Methods: A total of 10 samples of powdered herbal medicine containing turmeric rhizome were collected from five sub-districts in Medan City (Medan Johor, Patumbak, Deli Tua, Medan Baru, and Medan Polonia) using simple random sampling technique. Sample extraction was carried out by maceration using 96% ethanol solvent. Qualitative analysis of curcuminoids was performed using Thin Layer Chromatography (TLC) method with chloroform:methanol (95:5) as mobile phase and curcumin standard as comparison. Determination of curcuminoid levels was conducted using UV-Vis Spectrophotometry method at a maximum wavelength of 425 nm. Results: Qualitative analysis results showed that all samples were positive for curcuminoids, indicated by Rf values close to or equal to the Rf value of curcumin standard (0.78), ranging from 0.76-0.82. The quantitative analysis results showed that among the ten samples tested, three samples (SJ-A 0.66%, SJ-B 0.29%, and SJ-I 0.28%) had curcuminoid levels below the minimum requirement, while seven other samples (SJ-C 5.73%, SJ-D 7.50%, SJ-E 9.13%, SJ-F 5.94%, SJ-G 4.66%, SJ-H 8.02%, and SJ-J 6.07%) met the requirements. Conclusion: All samples of powdered herbal medicine containing turmeric rhizome circulating in Medan City were positive for curcuminoids; however, three out of ten samples (30%) did not meet the quality requirements for curcuminoid levels according to the Indonesian Herbal Pharmacopoeia Second Edition 2017, which specifies not less than 3.82%. This indicates the need for more stringent quality control of herbal medicine products circulating in the community.